The simulation of biogas combustion in top open burner - Selvam, A.; Noor, M. M.; Norhafana, M.; Ihsan, C. K.; Khalid, A.; Mahmood, R. A.; Harikrishnan, S.; Nayak, S. (IOP Publishing, 2024)
The top open furnace is commonly used for the heating processes. The efficiency of the top open furnace is low due to the amount of heat wasted through the top open. This study was using ANSYS Fluent, a two-dimensional computational fluid dynamic (CFD) model that was used to build the top open furnace. Exhaust gas recirculation (EGR) was installed in the boiler in order to collect the exhaust gas and reuse it to dilute the oxygen supply. To check the combustion of low calorific gas (LCV) gas, which is biogas composed of 60% methane and 40% carbon dioxide by mass fraction, the computational study started with a standard combustion with EGR. Medium-sized mesh is used for the smoothing grid. This mesh uses inflation to enable the size of the cells and the stack element. The findings of the numerical sensitivity test show that the boundary conditions along the combustion chamber wall can affect the flame temperatures. The MILD regime was reached using biogas fuels when the right parameters were used.